2012
DOI: 10.1177/1049909112440836
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of Care of Children at End of Life

Abstract: Parental satisfaction with their child's care during end of life indicates need for improvement in pain management, communication, and parental involvement in decision making. While education cannot guarantee desired changes in attitudes or behaviors, it may provide the essential foundation of knowledge, skills, and ethical understanding needed by professional providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 26 publications
1
39
0
16
Order By: Relevance
“…5 professionals are recognized as determinants of providing high-quality paediatric palliative care [14][15][16] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 professionals are recognized as determinants of providing high-quality paediatric palliative care [14][15][16] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…61 Parents have shared that they felt sibling support groups and bereavement follow-up was lacking and sorely needed. 62,63 Spiritual The spiritual dimension of pediatric palliative care refers to how the child understands the meaning of an experience. 19 Spirituality comes into focus when an individual faces emotional stress, physical illness, or death.…”
Section: Socialmentioning
confidence: 99%
“…This service provides families an opportunity to share their grief with others who have experienced the same kind of loss and to reconnect with the staff members who cared for their child, a need that has been repeatedly identifi ed in the literature. 8,10,12,19,21,66 The service includes music, poetry, sharing memories, art projects sponsored by the Arts in Medicine program, and release of live butterfl ies to honor the memory of the children.…”
Section: Ongoing Support and Lasting Communicationmentioning
confidence: 99%
“…9,12,18,42,43,46 Feedback from bereaved parents has indicated that families often do not know it is appropriate to cut a lock of hair or take pictures until the possibility is suggested to them and have later regretted not doing so. 21,43 Procedures for organ and tissue donation, involvement of a medical examiner, and handling the child's body should be explained to the family with sensitivity, by using language that distinguishes between the human body and the child's spirit. 30 On occasion, families may request to transport the body themselves to the funeral home.…”
Section: Explanationmentioning
confidence: 99%
See 1 more Smart Citation